Kinerja Continuous Electrochemical Clarifier (CEC) sebagai Teknologi Pengolahan Air Sumur Berkadar Besi dan Mangan Tinggi Menjadi Air Bersih - Suhirman Suhirman; Tubagus Fadhli Robby; Mutia Amyranti (UNIVERSITAS ISLAM SYEKH YUSUF TANGERANG, 2026)
Groundwater from the Klawas area, Muara Enim, South Sumatra, at a depth of approximately ?110 m, exhibits a reddish-brown coloration, indicating high concentrations of iron (Fe) and manganese (Mn). Preliminary analysis showed that the water quality did not meet the clean water standards stipulated in Regulation of the Indonesian Ministry of Health (Permenkes) No. 2 of 2023, as indicated by a turbidity of 30.1 NTU, TDS of 18.6 mg/L, Fe concentration of 3.5 mg/L, Mn concentration of 0.55 mg/L, and the presence of E. coli (25 MPN/100 mL) and total coliform (5 MPN/100 mL). Water treatment was conducted using a Continuous Electrochemical Clarifier (CEC) with a capacity of 3 m?/h, consisting of three main stages: aeration as primary treatment, an electrochemical clarifier to reduce turbidity and TDS, and silica filtration followed by electrodisinfection to remove pathogenic microorganisms. The Continuous Electrochemical Clarifier (CEC) system proved effective in treating groundwater from Klawas into clean water that complies with Permenkes No. 23 of 2017 and Permenkes No. 02 of 2023. The aeration unit reduced iron and manganese concentrations to <0.001 mg/L and <0.1 mg/L, respectively, while the clarifier operated at an optimum dose of 350 Farad and the filtration unit reduced turbidity and TDS to <0.001 ? 0.01 NTU and 12.50 ? 0.10 mg/L. In addition, the electrodisinfection unit successfully eliminated E. coli and total coliform to 0 MPN/100 mL.